Areas of polygons on lattices - Tatyanenko A. A. (Summer Vacation, 2016)
this article presents basic methods of areas of polygons on lattices calculating. The authors considered in detail and illustrated with examples the formula of Pick, beyond the scope of the school program.
Keywords: многоугольник; площадь многоугольник; формула Пика; polygon; plygon area; Pick's formula